Homeopathic preparations on thrips control, Thrips tabaci Lind (Thysanoptera: Thripidae), in onion organic cropping system - Gonçalves, Paulo Antonio de Souza (Revista de Ciências Agroveterinárias, 2007)
The objective of this research was to evaluate the effect of homeopathic preparations to control thrips, Thrips tabaci Lind. (Thysanoptera: Thripidae), on onion produced using an organic cropping system. The research was carried out Ituporanga, Santa Catarina State, Brazil, during 2003, 2004 and 2006. Treatments were: wormwood, Artemisia verlotorum, 3CH and 30CH, tartar emetic 30CH, Bordeaux mixture 5% 3CH and 30CH, lime sulfur 5% 30CH, Staphisagria 8CH and 32CH, lime sulfur 5% 3CH, Bioalho® 3CH, triple superphosphate 3CH, neem, Azadirachta indica, leaf extract 3CH, extract of fodder radish, Raphanus sativus var. oleiferus, 3CH, shell lime 3CH, earth diatomaceous 3CH, Sulphur 3CH, plant damaged for onion thrips, T. tabaci and downy mildew, Peronospora destructor, 3CH, phosphate rock 3CH, ammonium nitrate 3CH, NPK 5-20-10 3CH, iron sulphate 3CH. Treatments did not differ significantly in relation to insect incidence, yield and mean bulb weight. Treatment’s percentage efficacy was low, ranging from 0% to 13.6%. The correlation between thrips incidence, yield and mean bulb weight was not significant.